PERENCANAAN SISTEM KENDALI MODEL REFERENCE - Al, Al; Rahmawati, Gusri; Premadi, Aswir; Effendi, Asnal (Jurnal Teknologi dan Vokasi, 2024)
The commercial use of drones has increased rapidly in this sector in the last few decades, one of which is the Hexacopter Type Unmanned Aerial Vehicle (UAV). Hexacopter is a flying robot without a pilot that can be controlled manually using a remote control and controlled automatically or on autopilot. The advantage of the hexacopter is its ability to maneuver flexibly, it can move in 8 cardinal directions without needing to turn first. However, despite their advantages, certain hexacopters must continue to fly stably under a variety of changing conditions, such as changing weather, different loads, or changing environmental conditions. For this reason, a control system is needed that is able to adapt to these changes. This condition makes it interesting to carry out experimental and simulation studies, namely designing a hexacopter with Model Referene Adaptive Control (MRAC) control. By using a Model Reference Adaptive Control (MRAC) control system with the main control using PID control, the response given is good and optimal, the system parameters reach the values: rise time (ts) 1.0709 s, delay time (td) 0.99 s, peak time (tp ) 2.6600 s, settling time (ts) 3.9351 s, overshoot (mp) 4.0847 and steady state error 0.0001%. The mathematical analysis of the MRAC control system needs to be studied in more depth so that the MRAC control calculations become more accurate.